Pricing and Inventory Control in Dual-channel Network with One Manufacturer and Retailer - PAN, Zhicong (Institutional Knowledge at Singapore Management University, 2010)
The study on multi-channel problems has been one of the most active research fields in recent years. In this paper, we consider a dual-channel network problem with one manufacture and one retailer. The manufacturer, acting as the Stackelberg leader, sells a single type of product through a traditional channel to the retailer and/or through a direct channel to customers. The retailer, acting as the follower, operates a Newsvendor model, ordering from the manufacturer and selling to the customers. We study the problem with the deterministic demand. We develop an efficient algorithm to find the joint optimal policy for three prices: the wholesale price, the retail price in the traditional channel and the selling price in the direct channel. Our framework involves four different operational scenarios: the dual-channel scenario, the traditional-channel-only scenario, the direct-channel- only scenario, and the "equal pricing" scenario in which the wholesale price is equal to the selling price in the direct channel. We provide some criteria to identify different operational scenarios, and compare the performance of the four operational scenarios through numerical analysis. The scenario using dual channel possesses much more complementary effect between two channels than the performance in the "equal pricing" scenario. This observation calibrates some arguments based on the references only considering the "equal pricing" scenario. In addition, we have also examined a vertically integrated firm that operates a dual-channel supply chain. This vertically integrated firm is a centralized decision maker that decides two selling prices for the dual channels simultaneously. We have also compared the performance of the four scenarios with the performance of the integrated firm through numerical analysis. We also consider stochastic demands for the dual-channel problem with one manufacturer and one retailer. In addition to pricing decisions, the manufacturer and the retailer also make inventory decisions (The retailer decides order quantity.) in the stochastic-demand problem. In our model, we consider exogenous wholesale price. There are four decision variables in our model: the retailer price, the direct channel price, the production capacity of the manufacturer, and the order quantity of retailer. We have developed a mechanism based on the chain rule to obtain the solutions one by one for these four decision variables. Given the wholesale price and the selling price in direct channel, we have obtained the retailer's order quantity and the retail price in the traditional channel. We have also obtained the optimal inventory capacity and the optimal direct price for the manufacturer given the retailer's best response for its order quantity and retail price. we also describe the optimal policy and compare the performance with regards to the retailer's order quantity through numerical analysis. We find that the manufacturer's profit is convex over the retailer's safety stock (order quantity), which indicates that an unique optimal wholesale price may not exist to maximize manufacturer's profit.